Lectures upon Jonah: delivered at York, in the year of our Lord 1594 - King, John (J. Nichol, 1864)
A sermon preached at the funeral of John, Archbishop of York, November the 17th, 1594 -- A sermon preached in York, the seventeenth of November, 1595, being the Queen's day.